Evaluasi Gerakan Perlindungan Anak Terpadu Berbasis Masyarakat (PATBM) di Kelurahan Sei Jang Kota Tanjungpinang - Sri Ambar Rinah; Fitri dewi Wulandari; Muhammad Prayoga (STISIPOL Raja Haji, 2022)
The Office of Women's Empowerment, Child Protection and Community Empowerment of Tanjungpinang City (DP3APM) and Sei Jang Village in an effort to prevent violence against children in Sei Jang Village by carrying out the PATBM Movement. The problem that often occurs in Sei Jang Village in carrying out the PATBM Program is that if there are PATBM Program activities they tend not to attend to carry out violence prevention activities against children, this can result in the PATBM program in Sei Jang Village not running well and smoothly. The purpose of this study was to evaluate the PATBM movement in the Sei Jang sub-district, Tanjunginang City. To find out the above, the researcher used the operational concept put forward by Stuffbeam, namely the CIPP (Context, Input, Process and Output) model. The population in this study were 52 employees of DP3APM Tanjungpinang City and 10 people involved in PATBM in Sei Jang Village, Tanjungpinang City and 2 people or parents who got activities in the PATBM program in Sei Jang Village. The research method used was descriptive research with evaluative approach. The evaluative approach was used to evaluate the Community-Based Integrated Child Protection Movement in Sei Jang Village, Tanjungpinang City. Techniques and Tools Data collection uses observation and interview techniques, while data analysis techniques use triangulation techniques, namely data reduction, data presentation and drawing conclusions. Based on the results of research on the evaluation of the PATBM Movement in the Kelurahan Sei Jang, Tanjunginang City, the overall implementation has followed the applicable rules and regulations. However, PATBM and its activities are still not maximal in preventing violence against children. There are suggestions that can be conveyed, namely to increase activities in the PATBM Movement, namely with the aim that the community knows that violence against children is very dangerous for children, to carry out activities that can make people aware of the importance of preventing violence against children.